Identification of components of a comprehensive disability rehabilitative programme for adult people living with HIV: a scoping review - Moalosi, Sithembile Precious (My University, 2019)
Background: Currently, over seven million South Africans live with HIV. Although antiretroviral therapy has increased the life expectancy of people living with HIV, there is growing evidence of HIV-associated disability contributing to morbidity in this population. Several studies have been undertaken to describe HIV-related disabilities and the rehabilitative interventions in respect thereof. However, there is no comprehensive management programme for HIV-related disability. The purpose of this scoping study is to identify components of a comprehensive disability management programme for people living with HIV. Method: This study is a scoping review following the Joanna Briggs Institute’s Scoping Reviews Manual. A systematic search for literature was done on the Public Medline and the Cumulative Index to Nursing and Allied Health Literature databases. The studies sought had been conducted in multiple settings worldwide on adult people living with HIV. The methodological quality assessments had been done using relevant tools. Results: A total of 27 peer-reviewed studies met the inclusion criteria. A review of the literature showed how the impairments are linked to activity limitation and participation restrictions, and these aspects influence the manner in which rehabilitation should be undertaken. Interventions for the identified HIV-related disabilities included exercise training and massage therapy. These interventions improved muscle strength, quality of life, cardiorespiratory fitness, body composition, metabolic profile, and psychological outcomes. Conclusion: This scoping review highlights the HIV-related disability and interventions thereof. The study showed how the respective impairments are linked to activity limitations and participation restrictions and their influence on the manner in which rehabilitation should be undertaken. Rehabilitative interventions are safe and recommended as part of routine HIV care.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Science in Physiotherapy (Community). Johannesburg, February 2019